Treedent Ship Sdn.Bhd Organizational Behavior - Ragu, Devadharshni; Kee, Daisy Mui Hung; Mahendran, Jevethra; Bt Muhd Azran Chan, Sofia Syazwani; Selvam, Divyaadharshinee Tamil; Alshammari, Sara (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Diversity management is a process that create and maintain positive work environment where the similarities and differences of individuals are valued. However, every employer or employee at some point will encounter some problems at their work place. Our group has decided to choose Treedent Ship Sdn.Bhd to research about some of the problems face by the organization and to provide relevant solutions based on the problems. The reason behind choosing this company is because the information was easily accessible. Moreover, the methodology used by our group is interview and we found out that the company faces several serious problems among the organization. One of the problem encounters by this company is high stress jobs. This problem is related to a theory, known as job demand-control (JDC) model. Secondly, employees are not getting enough motivation to succeed in their performance. Lastly, job satisfaction that refers to unhappy or negative feelings about the work and work environment. The factors that lead to the job satisfaction will be explained further in the report. In conclusion, our group has come up with several recommendations that helps the company to solve those problems. The management and employees have to prioritize and plan the most important task in an organized way to reduce stress. Besides, the management has to empower and offer more opportunities for advancement to motivate the employees. Last but not least, job satisfaction can be improved by providing positive working environment, rewards and recognition to the employers and employees.